Diagnósticos do judiciário brasileiro e a trajetória adotada pelo direito processual civil para uma prestação efetiva - Freitas, Carolina Maria Gris de (2021)
To the extent that the demand for the Judiciary's intervention in society's conflicts has been maintained in recent years, the congestion of lawsuits pending consideration has also been maintained, which undermines the delivery of fair decisions within a reasonable term. In contrast to the constitutional model, which enshrines effective judicial protection, we have the crisis of efficiency in the provision of jurisdiction that frustrates the concretization of rights and leads to the discredit of the Judiciary itself. In view of this, there are questions regarding the historical collaboration of the Brazilian procedural system to solve the problem, especially due to the recurring changes suffered in our Brazilian procedural system and the current structure of the Judiciary. In this sense, the present work will address, from the diagnoses of the law and the Judiciary, the paths adopted by the Brazilian procedural system and procedural management in order to achieve an effective jurisdictional provision